The Role of Total Quality Management and Organizational Culture in Enhancing Employee Performance: Towards Sustainable Public Service Development - Marpaung, Rio (Journal of Ecohumanism, 2024)
This study explores the impact of Total Quality Management (TQM) on employee performance, focusing on the mediating role of organizational culture in fostering sustainable and human-centric development within public institutions. Conducted at the Pekanbaru State Asset and Auction Service Office (KPKNL), this research employs SEM-PLS to analyze data from 42 employees. The findings highlight the importance of integrating TQM with a supportive organizational culture to enhance both employee performance and institutional responsiveness to societal needs. The study contributes to the discourse on sustainable public service management by underscoring the value of quality-oriented and inclusive organizational practices.